Characteristics of lightning surges induced in telecommunication center in tropical area - Tominaga, Tetsuya; Kuwabara, Nobuo; Kato, Jun; Ramli, Annuar; Halim, A.; Ahmad, Hussein (IEEE, 2003)

(untitled)
The characteristics of lightning-induced surges in telecommunication equipment due to a direct lightning strike at a telecommunication center building or tower should be investigated to maintain the reliability of advanced telecommunication systems. In particular, investigations in tropical areas are important because these areas have many thunderstorm days. We observed lightning surges induced in a telecommunication building in Kuala Lumpur, Malaysia The results show that the peak value occurrence frequency and waveforms of direct strike lightning surges were almost the same as those in a temperate area. The peak current relationships between the cables in the building and the tower legs indicate a strong correlation between the current at the tower legs, waveguide, power line, and outer and inner conductors of the coaxial cables. However, the peak value correlations between the tower leg currents and interface cable voltages were not strong. Based on the observation results, we obtained the correlation factors between the peak value at the observation point and the tower legs, and calculated the peak value at the interface cables as a function of the number of thunderstorm days.